Different in vitro proliferation and cytokine‐production inhibition of memory T‐cell subsets after calcineurin and mammalian target of rapamycin inhibitors treatment. Issue 2 (29th March 2016) - Merino, David; San Segundo, David; Medina, Juan M.; Rodrigo, Emilio; Asensio, Esther; Irure, Juan; Fernández‐Fresnedo, Gema; Arias, Manuel A.; López‐Hoyos, Marcos
Summary: Calcineurin inhibitors (CNI) and mammalian target of rapamycin inhibitors (mTORi) are the main immunosuppressants used for long‐term maintenance therapy in transplant recipients to avoid acute rejection episodes. Both groups of immunosuppressants have wide effects and are focused against the T cells, although different impacts on specific T‐cell subsets, such as regulatory T cells, have been demonstrated. A greater knowledge of the impact of immunosuppression on the cellular components involved in allograft rejection could facilitate decisions for individualized immunosuppression when an acute rejection event is suspected. Memory T cells have recently gained focus because they might induce a more potent response compared with naive cells. The impact of immunosuppressants on different memory T‐cell subsets remains unclear. In the present study, we have studied the specific impact of CNI (tacrolimus) and mTORi (rapamycin and everolimus) over memory and naive CD4 + T cells. To do so, we have analysed the proliferation, phenotypic changes and cytokine synthesis in vitro in the presence of these immunosuppressants. The present work shows a more potent effect of CNI on proliferation and cytokine production in naive and memory T cells. However, the mTORi permit the differentiation of naive T cells to the memory phenotype and allow the production of interleukin‐2. Taken together, our data show evidence to support the combined use of CNI and mTORi in transplant immunosuppression.